Strategi Pengembangan Koleksi Fiksi Di Perpustakaan SMA Negeri 1 Bangko Kabupaten Rokan Hilir Dalam Meningkatkan Minat Kunjung Siswa - Tusadiah, Halimah; Batubara, Abdul Karim; Ali, M.Nasihudin (CV. ITTC INDONESIA, 2024)
This study aims to determine the utilization of fiction collections and strategies for developing fiction collections in the library of SMA Negeri 1 Bangko, Rokan Hilir Regency. This type of research is descriptive with a qualitative approach. Data collection techniques used for data collection are interview, observation, and documentation methods. While data analysis techniques go through three stages, namely, data reduction, data presentation, conclusion drawing and verification. This research was conducted at the Library of SMA Negeri 1 Bangko, Rokan Hilir Regency. The theory used in this study is branding theory. The results of this study are that in its use the fiction collection owned by the library has been used by library users / users in their daily activities to fill their spare time, as entertainment, motivation, and learning. The strategy of developing fiction collections used by the Library of SMA Negeri 1 Bangko, Rokan Hilir Regency is through promotion, procurement of library materials, and weeding (weeding library materials).